The Sterndale Bennetts: The Masquers Years (1933–1940) - Mann, George (Theatre Research in Canada / Recherches théâtrales au Canada, 2000)
This paper analyses the theatrical activities of Ernest and Belle Sterndale Bennett in and around Toronto prior to Belle’s death in 1936 as well as Ernest’s continuing accomplishments through 1940. It illustrates the Sterndale Bennetts’ major concerns – to achieve quality theatrical performance and to help raise theatrical standards in Canada. To a certain extent, they achieved this end while working with a group of amateurs made up of employees from the T. Eaton Company – a group known as the Masquers Club of Toronto. Through his work with the Masquers and other Ontario theatre societies, Ernest Sterndale Bennett developed into one of Canada’s most highly respected directors. Cet article analyse les activités théâtrales d’Ernest et de Belle Sterndale Bennett qui se sont passées à Toronto et ses alentours avant la mort de Belle à 1936, et qu’Ernest a continué jusqu’à 1940. L’article illustre les grandes lignes de l’entreprise des Sterndale Bennett – d’acquérir l’excellence dans les représentations théâtrales et d’augmenter les standards au théâtre canadien. Jusqu’à un certain point ils ont achevé leur but en travaillant avec un groupe d’amateurs formé d’employés de la compagnie T. Eaton - un groupe connu sous le nom de "Masquers Club of Toronto." Grâce à son travail avec les "Masquers," et avec d’autres sociétés théâtrales d’Ontario, Ernest Sterndale Bennett devint un des metteurs en scène le plus respecté au Canada.